Analisis Keselamatan dan Kesehatan Kerja (K3) untuk Meminimalisir Potensi Bahaya Menggunakan Metode Job Safety Analysis (JSA) di UMKM Bleduk Jati - Ali Asnawi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze potential hazards in the production process of Bleduk Jati MSMEs through the application of the Job Safety Analysis (JSA) method to strengthen occupational safety and health efforts. Hazard identification was carried out by mapping all stages of work, collecting primary data through questionnaires, and confirming field conditions using supporting documentation. Risk scores were obtained from a combination of frequency and severity values, which were then summarized in a risk matrix to determine the hazard category for each production process. The results showed that several activities, such as cutting, baking, and smoothing, had high to extreme levels of danger, especially those involving direct contact with machinery, exposure to heat, and material dust. These findings emphasize the importance of stronger control through technical improvements, the use of personal protective equipment, work area rearrangement, and increased worker understanding of safety procedures. The study concludes that the application of JSA provides a more structured overview of risks and can serve as a basis for developing safe work procedures for the operational sustainability of MSMEs.